2017
DOI: 10.5603/arm.2017.0006
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Gland in Chronic Obstructive Pulmonary Disease

Abstract: The risk of chronic obstructive pulmonary disease (COPD), as well as thyroid diseases increases with age. COPD is a common systemic disease associated with chronic inflammation. Many endocrinological disorders, including thyroid gland diseases are related to systemic inflammation. Epidemiological studies suggest that patients with COPD are at higher risk of thyroid disorders. These associations are not well-studied and thyroid gland diseases are not included on the broadly acknowledged list of COPD comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Thyroid dysfunction is associated with many changes in pulmonary physiology. [ 58 ] Clinical investigators have observed that OSAHS and hypothyroidism share several common clinical features, such as daytime sleepiness, slow reaction time, and memory decline. These features are commonly seen in both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid dysfunction is associated with many changes in pulmonary physiology. [ 58 ] Clinical investigators have observed that OSAHS and hypothyroidism share several common clinical features, such as daytime sleepiness, slow reaction time, and memory decline. These features are commonly seen in both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, Karadag et al [11] found a positive correlation between interleukin 6, which is a systemic inflammation marker, and total triiodotironine (TT3) and TT3/TT4 (total tyhroxine) in patients with stable COPD [11]. Smoking increases systemic inflammation independently from associating COPD and may affect thyroid functions [12]. Higher levels of serum total triiodothyronine (TT3) were found in young healthy smokers compared to non-smoking control subjects, which may suggest that smoking acts independently of coexistent diagnosis of COPD [13].…”
Section: Introductionmentioning
confidence: 93%